"I seriously wanted to opt for science, but they said no": visual impairment and higher education in India. Issue 2 (7th February 2021) - Palan, Ruchi
Abstract: The voice of disabled students in higher education (HE) has been widely explored in the global North but relatively little is known about the experiences of their counterparts in the global South. The paper attempts to address this lacuna by focusing on disabled students in HE in India. A part of the author's doctoral study in 2013–14 explored the lived experiences and aspirations of 29 students with a visual impairment using phenomenological methodology. Their access to courses and subsequently, career opportunities were found to be restricted by an interplay of systemic exclusion, lack of information, internalised oppression, pedagogy, and employment opportunities. While disability legislation in India focuses on widening participation in HE, the issue of access to courses for students with a visual impairment has received little attention. This paper emphasises the importance of facilitating their access to their desired courses in HE and to this end, provision of support in school. Points of interest: This article highlights the experiences of students with a visual impairment regarding enrolling in different courses in higher education (HE) in India. The research found that four main factors prevented many students with a visual impairment from pursuing science-and mathematics-based courses in HE. These were i) exclusion from science and mathematics in early education, ii) inadequate support systems, iii) inaccessible teaching practices, and iv) limited work opportunities. Little or no support and motivation was available for them to study these subjects. The research recommended that HE authorities must recognise the ability of students with a visual impairment to learn visual-based subjects. It also highlighted the need to provide support for learning mathematics and science to these students in school so that they can study mathematics- and science-based courses in HE.